PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP PRODUKTIVITAS KARYAWAN DENGAN MEDIASI MOTIVASI KERJA - Nazda Tazkia; Daman Sudarman (Media Riset Bisnis Manajemen Akuntansi, 2026)
This study examines the influence of competence and compensation on employee productivity, with work motivation as a mediating variable, in outsourcing companies in DKI Jakarta. The research addresses the gap regarding inconsistent findings in the relationship between these variables, especially within the specific context of outsourced labor. A quantitative approach was employed using a causal-associative design. Data were collected via questionnaires from 396 outsourced employees across six manpower supply companies of varying scales (large, medium, small). The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that: (1) competence has a positive and significant effect on compensation; (2) both competence and compensation positively and significantly affect work motivation; (3) competence and work motivation directly and positively affect employee productivity; (4) compensation has no significant direct effect on productivity; (5) work motivation fully mediates the effect of compensation on productivity and partially mediates the effect of competence on productivity. The findings emphasize that developing employee competence is the primary driver, while compensation influences productivity indirectly by enhancing work motivation. Keywords : Competence, Compensation, Work Motivation, Employee Productivity, Outsourcing, PLS-SEM.